Disclosure of New Health Problems and Intervention Planning Using a Geriatric Assessment in a Primary Care Setting - Mueller, Christiane Annette (Croatian Medical Schools, 2010)
AIM: To determine the prevalence of health problems uncovered by a Standardized Assessment for Elderly Patients in a Primary Care Setting (STEP), to explore how often STEP uncovered conditions new to general practitioners (GP) and ascertain how often STEP results led GPs to plan further interventions. METHODS: This descriptive, interim analysis was based on the data of 189 elderly patients (median age, 78 years; interquartile range [IQ], 74-81) and their 20 GPs collected in Hannover region, Germany, between June 2008 and April 2009. Study nurses in the practice setting applied the 44-item STEP instrument, based mainly on self-reporting, as well as a standardized patient interview. Subsequently, GPs indicated whether the problems were new to them, and whether they planned further action or health interventions on the basis of the problems identified by STEP. RESULTS: A median of 11 health problems (IQ, 8-14) were uncovered per patient, of which a median of 2 (IQ, 1-4) were new to the GP and interventions were planned for a median of 2 problems (IQ, 0-4). Many of the identified health problems are typical of old age. The following health problems uncovered by STEP were often new to the GPs (percentages differ to numbers due to missing GP ratings): cognitive impairment (33 of 64 affected by this problem, 73%), missing or unknown immunization status (84 of 160, 55%), and recent chest pain (19 of 37, 53%). Alcohol misuse was new in all 4 affected patients (100%) and recent falls were new in 5 of 7 patients (83%). Interventions for affected patients were frequently planned for problems of immunization (for 83 patients of 160 reporting the problem, 57%), current anxiety (4 of 9, 50%), and chest pain (14 of 37, 44%). Moreover, further management was frequently planned for depression (10 of 29, 39%) and cognitive impairment (16 of 64, 38%). CONCLUSION: Using a geriatric assessment in primary care discloses relevant heath problems and treatment needs that GPs may otherwise overlook. REGISTRATION NUMBER: DRKS00000575